Le vote féminin et la transformation des colonies françaises d’Amérique en départements en 1946 - Clara Palmiste (Nuevo mundo - Mundos Nuevos, 2014)
After the liberation of France and the restoration of republican legality, the French Empire had to be organized. It was during this period of transformation that the right to vote was granted to women on April 21st, 1944. The 1945 elections were a major issue because the colonial representatives to the constituent assembly would influence the fate of the French West-Indian territories. Although the female vote seemed secondary in this context, it could significantly tip the balance in favor of the party that supported or not the French policies of assimilation.The first part of this paper aims to analyze the preparation and significance of women’s participation in the 1945 elections in the French Antilles. The second part examines women’s standpoints about women’s vote and their view on départementalisation, by focusing on three women: two deputies from Guadeloupe: Eugénie Eboué-Tell and Gerty Archimède and an intellectual woman from Martinique: Paulette Nardal. Was women’s vote decisive for the transformation of the colonies into overseas départements?